PID: An integrative and comprehensive platform of plant intron. (August 2021) - Gao, Ying; Ge, Fangfang; Zhang, Rui.; Yin, Deyou; Zhao, Ying; Tang, Heng; Zhang, Li; Yang, Long
Graphical abstract: Highlights: PID is a platform to identify, query and browse plant introns. A plant intron database of 118 species, 24, 782, 048 introns, 30, 843, 049 exons, and 414 visual maps. A detail information of the length distribution, GC content and base preference of introns in plants. Abstract: Intron is a non-coding sequence of a broken gene and participates in important biological processes, such as transcription regulation, alternative splicing, and nuclear export. With the development of plant genomes, a comprehensive platform for intron analysis in plants must be established. Plant Intron Database (PID), a publicly available searchable database, was developed to efficiently store, query, analyze, and integrate intron resources in plants. The information of intron, exon, and gene can be searched by key words in PID. Users cannot only view intron length distribution pie chart and 5′ and 3′ splice site sequence feature maps in a statistical interface but can also browse intron information in a graphical visualization interface through JBrowse. ViroBlast for sequence homology searches, Intron detection and sequence interception tools were also provided. PID contains annotated genes from 118 sequenced plants, 24, 782, 048 introns, 30, 843, 049 exons, and 414 visual maps. This tool will greatly accelerate research on the distribution, length characteristics, and functions of introns in plants. PID is accessible at http://biodb.sdau.edu.cn/PID/index.php .